Improved Leadership Transformational With Organizational Citizenship Behavior (OCB) - Nur Alifah; Agus Rohmat Hidayat; Agis Ahmad Rodiansjah (Syntax Idea)
The role of leadership is very strategic and important for the achievement of the mission, vision and goals of an organization, is one of the motives that encourage humans to always investigate the intricacies associated with leadership. Transformational leadership basically encourages subordinates to do better Behavior demanded by today's organizations is not only in-role behavior but also extra- role behavior. Extra-role behavior is also called the Organizational itizenship Behavior.OCB is a term used to identify the employee behaviors that can be called a "good employee". If employees in the organization have OCB, efforts to control employee declined, since employees can control their own behavior or being able to choose the best behavior for the benefit of the organization. OCB will enhance transformational leadership because the good nature of OCB will influence the behavior of the leader. There is a significant influence ith the value of P = 0.00 between OCB and transformational leadership. This shows there is an increase in transformational leadership due to OCB behavior